EMOTIONS AND HYPERTENSION: THE INTRODUCTION OF A COGNITIVE-BEHAVIORAL PROGRAM FOR HYPERTENSIVE PATIENTS - Miguel-Tobal, Juan José; Cano-Vindel, Antonio; Casado Morales, Mª Isabel; Escalona Martínez, Amalia (Anales de Psicología / Annals of Psychology)
In the present paper a multicausal perspective for explaining the onset and maintenance of arterial hypertension is supported, standing out emotional variables as risk factors. A cognitive-behavioral program for hypertension control is presented, in which different therapeutic procedures were combined: information sessions, progressive muscular relaxation training, respiration techniques, problem-solving strategies, and self-control techniques for life habits change. Results showed modifications in the majority of the psychological variables treated (anxiety, anger, problem-solving resources, etc), as well as strong decreases in blood pressure levels, varying the treatment group mean scores from systolic: 151mm/HG and diastolic: 94mm/Hg in pre-treatment assessment to systolic: 132mm/hg and diastolic: 81mm/Hg at post-treatment assessment. These changes are highly statistically as well as clinically significant.